A pervious concrete incorporating waste glass powder and a method of making the same

By adding waste glass powder and coal gangue into permeable concrete, optimizing the pore structure and generating CSH gel, the problems of frost resistance and sulfate erosion resistance of permeable concrete in cold and saline areas are solved, efficient resource utilization is achieved, and the permeability and mechanical properties of concrete are improved.

CN120518351BActive Publication Date: 2025-10-17CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511041621.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-28
Publication Date
2025-10-17
Estimated Expiration
2045-07-28

AI Technical Summary

Technical Problem

Existing permeable concrete has poor frost resistance and sulfate corrosion resistance when used in cold and saline areas. It is difficult to balance permeability and mechanical properties, and the utilization rate of solid waste resources is low.

Method used

A permeable concrete formula that incorporates waste glass powder and coal gangue is adopted. The coal gangue provides a strength skeleton, the waste glass powder optimizes pore connectivity, and reacts synergistically with silica fume to generate CSH gel, enhancing the interface transition zone and achieving efficient resource utilization.

Benefits of technology

It significantly improves the engineering applicability and environmental benefits of permeable concrete, enhances its resistance to freeze-thaw cycles and sulfate erosion, and at the same time increases the resource utilization rate of waste glass and coal gangue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120518351B_ABST
    Figure CN120518351B_ABST
Patent Text Reader

Abstract

The application discloses a kind of waste glass powder doped pervious concrete and preparation method thereof, belong to concrete technical field.The application will waste glass powder partially replace cement, accelerate cement hydration, coal gangue is used as aggregate to optimize pore structure, realize the efficient resource utilization of waste glass and coal gangue;The waste glass powder content of 10% of the pervious concrete not only can pass through the double solid waste synergistic effect to improve the strength of pervious concrete, frost resistance and key performance such as sulphate attack resistance, but also can greatly improve the resource utilization rate of waste glass, coal gangue, reduce ordinary aggregate and cement consumption.This innovation not only breaks through the performance limitation of traditional pervious concrete, but also opens up a new path for bulk solid waste recycling, and has social and economic benefits and sustainable development prospects in the field of environmental protection and resource conservation.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of concrete, and particularly relates to a pervious concrete mixed with waste glass powder and a preparation method thereof. BACKGROUND

[0002] In the process of rapid urbanization, the extensive laying of traditional impervious pavement has caused a series of environmental problems. As an eco-friendly building material, pervious concrete has a porous structure and excellent water permeability, can quickly penetrate rainwater, replenish groundwater, regulate temperature and humidity to alleviate the heat island effect, and can improve the skid resistance of the pavement, and has a broad application prospect in urban construction. However, the application of pervious concrete in cold and saline areas encounters difficulties. Although the porous structure of pervious concrete is beneficial to water permeability, it is not resistant to freeze-thaw cycles and sulfate attack. The expansion stress caused by the phase change of pore water during freeze-thaw will cause the expansion of micro-cracks in the concrete and the attenuation of strength; sulfate attack further aggravates the internal damage by ion penetration and reaction with cement hydration products to generate expansive crystals, greatly shortening the service life of the material. How to coordinate the water permeability, mechanical properties and durability has become the core challenge of its technological upgrading.

[0003] At the same time, the resource utilization of industrial solid waste in China is urgent. Coal gangue, as the main byproduct of the coal industry, has a huge annual discharge amount, not only occupies a large amount of land, but also pollutes the soil, water and air due to open-air stacking. Coal gangue is used as an aggregate replacement material in the building materials field, but its high-value utilization technology needs to be broken through. At present, a large amount of waste glass is generated in China every year, but the overall recycling rate is low, and most of it is landfilled. Waste glass has high chemical stability and volcanic ash activity, and its powder can be used as a cement replacement material to reduce carbon emissions, but its application in pervious concrete systems is less studied, and the synergistic potential with coal gangue has not been fully tapped.

[0004] In recent years, although there have been some progress in the field of solid waste-based pervious concrete in the academic field, such as using coal gangue to replace natural aggregate to improve the strength of concrete and confirming the optimization effect of glass powder on the mechanical strength of concrete, there are still many limitations in the existing technology. Single solid waste modification cannot balance the strength and durability, and high content of solid waste can easily lead to uncontrolled porosity, and there is no systematic solution for the synergistic improvement of frost resistance and sulfate resistance. SUMMARY

[0005] The technical problem to be solved by the present application is to provide a pervious concrete mixed with waste glass powder and a preparation method thereof, to solve the technical problem of poor frost resistance and sulfate resistance of existing concrete.

[0006] To achieve the above-mentioned purpose, the technical scheme adopted by the present application is to provide a pervious concrete mixed with waste glass powder, wherein the content of the waste glass powder is 1m 3By volume, the following raw materials are included: 800-900 kg of natural aggregate, 430-652 kg of cement, 300-400 kg of coal gangue, 162-172 kg of water, 34-200 kg of waste glass powder, and 33-35 kg of silica fume. The total solid waste ratio is 16.49%-28.67%. The standard consistency of cement is 26.7%, and the specific surface area is 387 m 2 / kg.

[0007] On the basis of the above technical solution, the present invention can also be improved as follows:

[0008] Further, with 1m 3 By volume, the following raw materials are included: 837.46 kg of natural aggregate, 575 kg of cement, 358.91 kg of coal gangue, 170 kg of water, 100 kg of waste glass powder and 34 kg of silica fume, with the total solid waste accounting for 22.11%.

[0009] Further, with 1m 3 By volume, the following raw materials are included: 800kg of natural aggregate, 652kg of cement, 300kg of coal gangue, 172kg of water, 34kg of waste glass powder and 35kg of silica fume, with the total solid waste accounting for 16.76%.

[0010] Further, with 1m 3 By volume, the following raw materials are included: 900kg of natural aggregate, 430kg of cement, 400kg of coal gangue, 162kg of water, 200kg of waste glass powder and 33kg of silica fume, with the total solid waste accounting for 28.24%.

[0011] Furthermore, the natural aggregate is crushed stone with a particle size of 5-15 mm, a mud content of 1.56%, a water absorption rate of 1.13%, a moisture content of 0.97%, and an apparent density of 2716.24 kg / m 3 , loose bulk density is 1581.2kg / m 3 , the compacted density is 1619.2kg / m 3 , the crushing index is 9.86%.

[0012] Furthermore, the particle size of the gangue is 5-15 mm, the mud content is 1.49%, the water absorption rate is 4.45%, the moisture content is 1.08%, and the apparent density is 2589.83 kg / m 3 , loose bulk density is 1258.4kg / m 3 , the compacted density is 1379.7kg / m 3 , the crushing index is 18.6%.

[0013] Further, the waste glass powder includes, in mass percentage: 70-75% SiO2, 10-15% Na2O, 5-10% CaO, 1-2% Al2O3, 0.5-1% K2O, 0.05-0.1% Fe2O3 and 3-4% impurities; the smooth surface of the waste glass powder can reduce the thickness of the paste wrapping the aggregate, and indirectly increase the effective porosity.

[0014] Further, the silica fume includes, in mass percentage: 90-98% SiO2, 0.5-1.3% Na2O, 0.2-0.4% Al2O3, 0.05-0.15% CaO, 0.05-0.15% MgO, 0.05-0.1% Fe2O3 and 1-8% impurities.

[0015] In the present application, the coal gangue (300-400 kg) is compounded with the natural aggregate (800-900 kg), the natural aggregate (broken stone) provides a strength skeleton, the coal gangue fills the secondary pores, and the waste glass powder optimizes the pore connectivity, so that the porosity and the connectivity meet the water permeable requirements. Meanwhile, the Al2O3 in the coal gangue and the SiO2 in the waste glass powder have a secondary reaction in an alkaline environment to generate hydrated calcium aluminum silicate (C-A-S-H), which enhances the interface transition zone. In the present application, the coal gangue partially replaces the natural aggregate, and the resource utilization rate of solid waste is increased by more than 30%.

[0016] The present application also discloses a preparation method of the water permeable concrete mixed with the waste glass powder, which comprises the following steps: mixing and stirring the natural aggregate, the coal gangue and 5-10 wt% of water for 20-40 s, then adding the cement, the waste glass powder and the silica fume, continuing to stir for 50-70 s, and finally adding the remaining water and stirring for 110-130 s to obtain the finished product concrete.

[0017] The present application has the following beneficial effects:

[0018] 1. In the present application, the waste glass powder partially replaces the cement, accelerates the cement hydration, the coal gangue optimizes the pore structure as the aggregate, and the efficient resource utilization of the waste glass and the coal gangue is realized. In the present application, the material system reconstruction (waste glass powder-coal gangue-silica fume synergy) and the precise proportioning control (80% reduction of the amount of silica fume and graded addition of the coal gangue) realize the dual breakthrough of the performance of the water permeable concrete and the resource utilization of the solid waste. These differences not only break through the boundaries of the prior art, but also reflect the creative leap from "material replacement" to "functional synergy", and significantly improve the engineering applicability and environmental benefits of the water permeable concrete.

[0019] 2、The prepared concrete maintains water permeability (water permeability coefficient is 0.25-0.66 cm / s), and the 28d compressive strength reaches 9-21 MPa, and the anti-freeze-thaw cycle times (25 times of strength loss is less than or equal to 20%) are better than the industry standard. The waste glass powder content of 10% of the pervious concrete not only can improve the strength, frost resistance and sulfate resistance of the pervious concrete through the synergistic effect of double solid wastes, but also can improve the frost resistance (strength loss rate is reduced by 22.9%) and sulfate resistance (strength loss rate is reduced by 37.2%), and can greatly improve the resource utilization rate of waste glass and coal gangue, and reduce the consumption of ordinary aggregate and cement. This innovation not only breaks through the performance limitations of traditional pervious concrete, but also opens up a new path for the recycling of bulk solid waste, and has social and economic benefits and sustainable development prospects in the field of environmental protection and resource conservation. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 XRD pattern of the concrete sample of Example 1-Example 5 and Comparative Example;

[0021] Figure 2 SEM image of the pervious concrete sample (comparative example) without glass powder under 100 times;

[0022] Figure 3 SEM image of the pervious concrete sample (comparative example) without glass powder under 1000 times;

[0023] Figure 4 SEM image of the pervious concrete sample (comparative example) without glass powder under 5000 times;

[0024] Figure 5 SEM image of the pervious concrete sample (Example 1) with 5% glass powder under 100 times;

[0025] Figure 6 SEM image of the pervious concrete sample (Example 1) with 5% glass powder under 1000 times;

[0026] Figure 7 SEM image of the pervious concrete sample (Example 1) with 5% glass powder under 5000 times;

[0027] Figure 8 SEM image of the pervious concrete sample (comparative example) without glass powder after 25 freeze-thaw cycles;

[0028] Figure 9 SEM image of the pervious concrete sample (Example 2) with 10% glass powder after 25 freeze-thaw cycles;

[0029] Figure 10SEM image of the pervious concrete sample without glass powder (comparative example) after 25 cycles of sulphate attack;

[0030] Figure 11 SEM image of the pervious concrete sample with 5% glass powder (example 1) after 25 cycles of sulphate attack;

[0031] Figure 12 SEM image of the pervious concrete sample with 10% glass powder (example 2) after 25 cycles of sulphate attack. DETAILED DESCRIPTION

[0032] The following describes the specific embodiments of the present application, so that those skilled in the art can understand the present application. The specific conditions are not specified in the examples, and are carried out according to the conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be purchased on the market. However, it should be clear that the present application is not limited to the scope of the specific embodiments. For those skilled in the art, it is obvious that various changes are within the spirit and scope of the present application as defined and determined by the appended claims, and all inventions using the concept of the present application are within the scope of protection.

[0033] In the following examples and comparative examples, the specifications of the components used are as follows:

[0034] The natural aggregate (crushed stone) was purchased from a building materials market in Chenghua District, with a particle size of 5-15 mm, a clay content of 1.56%, a water absorption of 1.13%, a water content of 0.97%, and an apparent density of 2716.24 kg / m 3 , a loose bulk density of 1581.2 kg / m 3 , a close bulk density of 1619.2 kg / m 3 , and a crushing index of 9.86%.

[0035] The standard consistency of the cement was 26.7%, and the specific surface area was 387 m 2 / kg.

[0036] The coal gangue was collected from a mining area in Liupanshui City, Guizhou Province, with a particle size of 5-15 mm, a clay content of 1.49%, a water absorption of 4.45%, a water content of 1.08%, and an apparent density of 2589.83 kg / m 3 , a loose bulk density of 1258.4 kg / m 3 , a close bulk density of 1379.7 kg / m 3 , and a crushing index of 18.6%.

[0037] Waste glass powder was collected from the Wannianchang tempered glass recycling station in Chenghua District, Chengdu City. Calculated by mass percentage, it includes: 72% SiO2, 13.1% Na2O, 8.91% CaO, 1.47% Al2O3, 0.83% K2O, 0.07% Fe2O3 and 3.62% impurities. The waste glass powder was refined to a powder state below 325 mesh (45μm) using a mechanical crushing process.

[0038] Silica fume comprises, by mass percentage, 96.74% SiO2, 0.99% Na2O, 0.32% Al2O3, 0.11% CaO, 0.1% MgO, 0.08% Fe2O3 and 1.66% impurities.

[0039] After crushing and screening the natural aggregate and coal gangue, the particle sizes of 5-10 mm and 10-15 mm are selected respectively and mixed in a mass ratio of 7:3 as the coarse aggregate component to be used so as to achieve the best porosity and connectivity.

[0040] Example 1

[0041] A permeable concrete mixed with waste glass powder, with a thickness of 1m 3 By volume, the following raw materials are included: 837.46 kg of natural aggregate, 614.51 kg of cement, 358.91 kg of coal gangue, 170.7 kg of water, 34.14 kg of waste glass powder and 34.14 kg of silica fume, with the total solid waste accounting for 19.17%.

[0042] The preparation method includes the following steps: mixing natural aggregate, coal gangue and 8wt% water for 30s, then adding cement, waste glass powder and silica fume, continuing to stir for 60s, and finally adding the remaining water and stirring for 120s to obtain finished concrete.

[0043] Example 2

[0044] A permeable concrete mixed with waste glass powder, with a thickness of 1m 3 By volume, the following raw materials are included: 837.46 kg of natural aggregate, 577.49 kg of cement, 358.91 kg of coal gangue, 169.85 kg of water, 67.94 kg of waste glass powder and 33.97 kg of silica fume, with the total solid waste accounting for 20.87%.

[0045] The preparation method of this embodiment is the same as that of Example 1.

[0046] Example 3

[0047] A permeable concrete mixed with waste glass powder, with a thickness of 1m 3By volume, the following raw materials are included: 837.46 kg of natural aggregate, 540.8 kg of cement, 358.91 kg of coal gangue, 169 kg of water, 101.4 kg of waste glass powder and 33.8 kg of silica fume, with the total solid waste accounting for 22.55%.

[0048] The preparation method of this embodiment is the same as that of Example 1.

[0049] Example 4

[0050] A permeable concrete mixed with waste glass powder, with a thickness of 1m 3 By volume, the following raw materials are included: 837.46 kg of natural aggregate, 504.42 kg of cement, 358.91 kg of coal gangue, 168.14 kg of water, 134.51 kg of waste glass powder and 33.63 kg of silica fume, with the total solid waste accounting for 24.22%.

[0051] The preparation method of this embodiment is the same as that of Example 1.

[0052] Example 5

[0053] A permeable concrete mixed with waste glass powder, with a thickness of 1m 3 By volume, the following raw materials are included: 837.46 kg of natural aggregate, 432.65 kg of cement, 358.91 kg of coal gangue, 166.41 kg of water, 199.69 kg of waste glass powder and 33.28 kg of silica fume, with the total solid waste accounting for 27.54%.

[0054] The preparation method of this embodiment is the same as that of Example 1.

[0055] Example 6

[0056] A permeable concrete mixed with waste glass powder, with a thickness of 1m 3 By volume, the following raw materials are included: 800kg of natural aggregate, 652kg of cement, 300kg of coal gangue, 172kg of water, 34kg of waste glass powder and 35kg of silica fume, with the total solid waste accounting for 16.76%.

[0057] The preparation method includes the following steps: mixing natural aggregate, coal gangue and 5wt% water for 40 seconds, then adding cement, waste glass powder and silica fume, continuing to stir for 50 seconds, and finally adding the remaining water and stirring for 130 seconds to obtain a finished concrete.

[0058] Example 7

[0059] A permeable concrete mixed with waste glass powder, with a thickness of 1m 3 By volume, the following raw materials are included: 900kg of natural aggregate, 430kg of cement, 400kg of coal gangue, 162kg of water, 200kg of waste glass powder and 33kg of silica fume, with the total solid waste accounting for 28.24%.

[0060] The preparation method comprises the following steps: mixing and stirring natural aggregate, coal gangue and 10wt% water for 20s, then adding cement, waste glass powder and silica fume, continuing to stir for 70s, and finally adding the remaining water and stirring for 110s to obtain finished concrete.

[0061] Comparative Example

[0062] A pervious concrete, 1m 3 by volume, comprises the following raw materials: natural aggregate 837.46kg, cement 651.84kg, coal gangue 358.91kg, water 171.54kg and silica fume 34.31kg.

[0063] The preparation method of the present comparative example is the same as that of Example 1.

[0064] The concrete of Examples 1-5 and the comparative example is used as a sample to prepare test pieces, and the following experiments are carried out.

[0065] 1. When preparing the compressive strength, water permeability coefficient, frost resistance and sulfate corrosion resistance test pieces, the mass of the material is weighed, the designed bulk density is determined according to the mixing ratio, the material is loaded into the test mold in two layers, and the material is inserted and tamped 16-30 times in each layer, at least 1 time in each corner, at least 2 times on each side, at least 4 times in the plane, and the insertion and tamping is as evenly distributed as possible, then a metal roller with a mass of 2kg is rolled back and forth along the four directions of the mold for 5 times.

[0066] 2. When preparing the flexural strength test piece, the material is loaded into the test mold in two layers, and the thickness of each layer is approximately the same, the material is inserted and tamped 52 times in each layer, at least 1 time in each corner, at least 11 times on each long side, at least 2 times on each short side, at least 22 times in the plane, and the insertion and tamping is as evenly distributed as possible, then a metal roller with a mass of 2kg is rolled back and forth along the four directions of the mold for 5 times.

[0067] Experimental Example 1 Microstructure Analysis

[0068] The SEM scanning electron microscope produced by Thermo Fisher Scientific Corporation of the United States and the DX-2700X-ray diffractometer are used for testing and analysis.

[0069] 1. XRD Analysis

[0070] Figure 1XRD patterns of the concrete samples of Example 1-Example 5 and Comparative Example; wherein G1 is Comparative Example, G2-G6 are Example 1-Example 5 respectively, the letter "S" represents SiO2, the letter "Ca" represents Ca(OH)2, the letter "C" represents C-S-H, and the letter "A" represents AFt. It can be seen from the XRD pattern analysis that, with the increase of the replacement ratio of waste glass powder to cement, the diffraction peak intensity of the main hydration product C-S-H phase presents a trend of first increasing and then decreasing. When the waste glass powder content is 5% (Example 1), 10% (Example 2) and 15% (Example 3), the active SiO2 in the glass powder reacts with the Ca(OH)2 generated by the hydration of cement to form additional C-S-H gel, resulting in a significant increase in the diffraction peak intensity, such as the peak at 29°. At the same time, the dissolution of aluminosilicate in coal gangue promotes the formation of aluminate phase, which is manifested by the enhancement of the characteristic peak in the range of 20°-30°.

[0071] However, when the glass powder replacement amount exceeds 20% (Example 4 and Example 5), the C-S-H peak intensity gradually decreases, which may be related to the insufficient cement clinker content and hindered hydration reaction caused by excessive glass powder. In addition, the increase of amorphous glass phase increases the background signal of the pattern, indicating that unreacted glass particles accumulate in the system. The incorporation of silica fume further optimizes the microstructure, which accelerates the early pozzolanic reaction and inhibits the combination of Ca(OH)2. Overall, the appropriate amount of glass powder optimizes the composition and degree of hydration products by synergizing the activity effects of coal gangue and silica fume, while excessive replacement leads to an increase in amorphous substances due to incomplete reaction, which has a significant correlation with the change trend of the mechanical properties of the material.

[0072] 2、SEM analysis

[0073] (1) Mechanical properties

[0074] Figures 2-4 SEM image of the pervious concrete sample without glass powder (Comparative Example). It can be seen from the SEM image that there are some small pores on the surface of the coal gangue aggregate, and the distribution is relatively scattered. Figure 2 When the magnification is increased to 1000 times ( Figure 3 ), some Ca(OH)2 crystals can be seen on the surface. When the magnification is increased to 5000 times ( Figure 4 ), it can be observed that some AFt is generated, which proves that the coal gangue pervious concrete can still maintain a certain good internal pore and smoothness of the mortar without glass powder and only with a small amount of silica fume.

[0075] Figures 5-7 SEM image of the pervious concrete sample with 5% glass powder (Example 1). After adding 5% glass powder ( Figure 5), the surface of the cement mortar is almost not observed to have tiny pores, and the flatness of the surface of the cement mortar is further enhanced, the main reason being that the glass powder has a small particle size and can play a micro-aggregate effect to fill in the tiny pores and further improve the internal pores of the pervious concrete. Figure 6 It can be found that the connection between the coal gangue aggregate and the mortar is relatively close, and there is no obvious crack and pore, which is because the glass powder and the silica fume not only have a filling effect to reduce the micro-pores between the connection surface of the aggregate and the mortar, but also increase the plastic viscosity of the cement paste to further promote the adhesion of the cement paste to the surface of the aggregate. Figure 7 It can be observed that there are many long and straight AFt staggered arrangements, which is because the glass powder and the silica fume contain acidic SiO2 components, which can react with the alkaline Ca(OH)2 formed by the hydration of cement, and at the same time, the alkalinity inside the pervious concrete is reduced, and the reduction of the alkalinity can inhibit the formation of the AFt (AFt) crystal to be thick and swelling. Therefore Figure 7 The long and straight AFt staggered in the middle phase will not reduce the strength of the pervious concrete, on the contrary, it can enhance the strength of the connection between the particles, so that the connection interface is more close.

[0076] (2) Frost resistance

[0077] Figure 8 and Figure 9 respectively are the SEM images of the pervious concrete samples with 0% (comparative example) and 10% (example 2) of glass powder after 25 freeze-thaw cycles. In the comparative example, the AFt is columnar, and the calcite is in a layered structure, which is loosely combined with the cement matrix; in example 2, the AFt crystal size is reduced, and the form is changed into a short rod, the thickness of the calcite is reduced, and the combination is more compact, which shows that the glass powder fills the pores to reduce the water migration, and by regulating the size of the AFt and the form of the calcite, the ice crystal expansion pressure is reduced.

[0078] (3) Sulfate resistance

[0079] Figures 10-12 respectively are the SEM images of the pervious concrete samples with 0% (comparative example), 5% (example 1) and 10% (example 2) of glass powder after 25 sulfate erosion cycles. From Figure 10 It can be observed that the surface structure of the comparative example is relatively loose, and a large amount of short and thick AFt is generated, which is because the comparative example does not add waste glass powder, and the pores of the concrete cannot be filled, the actual porosity is relatively high, so that the sodium sulfate solution can easily penetrate into the interior of the concrete, and then a large amount of AFt is generated. This kind of erosion product continuously accumulates and produces expansion and extrusion effect, which causes damage to the internal structure of the concrete, and obvious cracks are generated, so the comparative example without adding glass powder has weak erosion resistance.

[0080] Example 1 ( Figure 11 ) and example 2 (Figure 12 The micro surface of the pervious concrete of Example 1 is more compact, and although some gypsum can be observed, the gypsum particles are small and uniformly dispersed in the matrix. This is because the glass powder has a small particle size, which can fill the pores of the pervious concrete and form a dense layer on the surface; at the same time, the amorphous silicon dioxide contained in the glass powder reacts with the cement hydration product Ca(OH)2 to form C-S-H gel, which fills the internal pores of the concrete and refines the pore structure, thereby delaying the erosion process and improving the erosion resistance.

[0081] Performance test of experimental example 2

[0082] 1. The actual porosity is determined by the drainage method.

[0083] 2. After the preparation of the pervious concrete, the test piece is tested for 7d and 28d strength according to the “Standard Test Methods for Physical and Mechanical Properties of Concrete” (GB / T50081-2019) and “Standard Test Methods for Physical and Mechanical Properties of Concrete” (GB / T50081-2019).

[0084] 3. The permeability coefficient of the pervious concrete is determined by the custom test device according to the permeability coefficient determination method (constant head method) described in Appendix C of the specification “Pervious Pavement Brick and Pervious Pavement Panel” (GB / T25993-2010).

[0085] The experimental data are shown in Table 1.

[0086] Table 1 Strength, porosity and permeability coefficient data table of test piece

[0087]

[0088] The compressive strength (7d and 28d) and flexural strength (28d) of Example 1 are increased by 5.7%, 4.91% and 23.57% respectively compared with the comparative example, because the waste glass powder is rich in silicon dioxide (SiO2) and has potential pozzolanic activity, and the particles can react with the hydration products of tricalcium aluminate (C3A) and tricalcium silicate (C3S) in cement to generate C-S-H gel, enhance the strength of the interface transition zone, and thus improve the overall strength of the concrete. In addition, the micro aggregate effect of waste glass powder is significant, and its small particles can fill the internal pores of the concrete, improve the compactness and uniformity of the structure, and have a synergistic effect on the improvement of the compressive and flexural strength of the concrete.

[0089] The actual porosity and permeability coefficient of Example 2 decreased by 4.65% and 26.46% respectively compared with the comparative example, which still met the national standard. When the waste glass powder content increased from 0 to 10%, the active SiO2 contained in the waste glass powder would react with the Ca(OH)2 produced by cement hydration to generate additional C-S-H gel, which filled part of the micropores and made the structure more dense. At the same time, the waste glass powder content was low at this stage, and the particles were small, which could fill the gap between the cement paste and the aggregate at a low dosage, reduce the pore size and reduce the connectivity of the pores, thereby leading to a decrease in porosity.

[0090] When the waste glass powder content exceeded 15% (such as Example 4 and Example 5), the excessive pozzolanic reaction would consume a large amount of cement hydration products, resulting in a decrease in effective C-S-H gel in concrete, which in turn reduced the compressive strength. At the same time, the micro aggregate filling effect could improve the strength of the concrete, but its effect was limited and could not make up for the contribution of the replaced cement to the strength due to the reduction of hydration reaction. In addition, the waste glass powder content exceeding 15% would result in a decrease in cement paste content, a decrease in cement hydration products, and a decrease in pozzolanic reaction rate, ultimately leading to a rapid decrease in the strength of the pervious concrete.

[0091] 4. The automatic low-temperature freeze-thaw tester produced by Tianjin Gangyuan Experimental Instrument Factory was used to conduct freeze-thaw test (25 freeze-thaw cycles) according to the Standard Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T50082-2009), and the experimental data are shown in Table 2.

[0092] Table 2 Test results of anti-frost performance parameters

[0093]

[0094] With the increase of waste glass powder content, the compressive strength loss first decreased and then increased, and the strength loss rate of Example 2 reached the minimum value of 5.63%. This is because when the waste glass powder content is 5% to 10%, the glass powder particles are fine and can fill the micropores of the cement matrix, optimizing the pore structure and thus reducing the water permeation and ice expansion pressure. At the same time, the active SiO2 in the glass powder reacts with the alkali environment to generate C-S-H gel, which enhances the matrix density and improves the frost resistance. Compared with the pervious concrete without waste glass powder (comparative example), the strength loss rate decreased by 22.89%. When the waste glass powder content was 10%, the glass powder filling and cement hydration reached a balance, the pore structure was more uniform, and the closed pore proportion was higher, effectively blocking water migration and inhibiting freeze-thaw damage.

[0095] The mass loss rate of Example 2 is the smallest after 25 freeze-thaw cycles, which is 1.38%. The reason is that the pervious concrete generates temperature stress during the freeze-thaw cycle process, and after multiple freeze-thaw cycles, the temperature stress gradually exceeds the bonding force between the aggregates, causing damage and cracking on the surface or inside of the test piece, and the microcracks gradually expand, and the cement paste and aggregates locally peel off. After adding glass powder, water can be effectively blocked from entering the pores or microcracks, reducing the freezing expansion force caused by excessive low temperature, and showing a decrease in mass loss compared to the group without adding glass powder.

[0096] 5. The test method of dry-wet cycle is adopted, the instrument is DHG series 101-3BS electric heating air drying oven, and the sulfate erosion test (sulfate dry-wet cycle 25 times) is carried out according to the standard GB / T50082-2009 “Standard for testing methods for long-term performance and durability of ordinary concrete”. The experimental data is shown in Table 3.

[0097] Table 3 Test results of sulfate resistance performance parameters

[0098]

[0099] Compared with the comparative example, the mass loss rate and strength loss rate of Example 2 are smaller in the sulfate resistance test, which are reduced by 15.84% and 37.21% respectively. This is because the micro-filling effect of glass powder refines the pores of concrete, inhibits the invasion of sulfate ions, and delays the erosion process. At the same time, the active silicon dioxide in waste glass powder will react with Ca (OH) 2 generated by cement hydration to reduce the content of free Ca (OH) 2 in cement stone, thereby inhibiting the reaction of sulfate ions and Ca (OH) 2 to generate expansive gypsum and reducing the risk of expansion damage.

[0100] When the waste glass powder content increases to 15% (Example 3), excessive addition leads to insufficient cement hydration, and the brittleness of concrete increases. Under the action of sulfate dry-wet cycle, the degree of deterioration may be intensified, and the compressive strength loss rate increases. This is because the higher the waste glass powder content, the more cement is replaced, and the amount of erosion products generated by the reaction of cement hydration products and SO4 2- increases, thereby causing the mass loss rate to increase.

[0101] From the above data, it can be seen that the concrete prepared by the present application with a waste glass powder content of 10% has significant advantages in mechanical properties, frost resistance and sulfate resistance, and has excellent mechanical properties and frost and sulfate resistance, providing an important reference for large-scale popularization and application.

Claims

1. A permeable concrete containing waste glass powder, characterized in that: 1m 3 Volumetric, including the following ingredients: 800-900kg of natural aggregate, 430-652kg of cement, 300-400kg of coal gangue, 162-172kg of water, 34-200kg of waste glass powder and 33-35kg of silica fume, with a total solid waste ratio of 16.49%-28.67%; the standard consistency of the cement is 26.7% and the specific surface area is 387m 2 / kg; the silica fume comprises, by mass percentage, 90-98% SiO2, 0.5-1.3% Na2O, 0.2-0.4% Al2O3, 0.05-0.15% CaO, 0.05-0.15% MgO, 0.05-0.1% Fe2O3 and 1-8% impurities.

2. The permeable concrete containing waste glass powder according to claim 1, characterized in that: 1m 3 By volume, the following raw materials are included: 837.46 kg of natural aggregate, 575 kg of cement, 358.91 kg of coal gangue, 170 kg of water, 100 kg of waste glass powder and 34 kg of silica fume, with the total solid waste accounting for 22.11%.

3. The permeable concrete containing waste glass powder according to claim 1, characterized in that: 1m 3 Volumetric, including the following ingredients: 800kg of natural aggregate, 652kg of cement, 300kg of coal gangue, 172kg of water, 34kg of waste glass powder and 35kg of silica fume, with a total solid waste proportion of 16.76%.

4. The permeable concrete containing waste glass powder according to claim 1, characterized in that: 1m 3 By volume, the following raw materials are included: 900kg of natural aggregate, 430kg of cement, 400kg of coal gangue, 162kg of water, 200kg of waste glass powder and 33kg of silica fume, with the total solid waste accounting for 28.24%.

5. The permeable concrete containing waste glass powder according to claim 1, characterized in that: The natural aggregate is crushed stone with a particle size of 5-15 mm, a mud content of 1.56%, a water absorption rate of 1.13%, a moisture content of 0.97%, and an apparent density of 2716.24 kg / m 3 , loose bulk density is 1581.2kg / m 3 , the compacted density is 1619.2kg / m 3 , the crushing index is 9.86%.

6. The permeable concrete containing waste glass powder according to claim 1, characterized in that: The coal gangue has a particle size of 5-15 mm, a mud content of 1.49%, a water absorption rate of 4.45%, a moisture content of 1.08%, and an apparent density of 2589.83 kg / m 3 , loose bulk density is 1258.4kg / m 3 , the compacted density is 1379.7kg / m 3 , the crushing index is 18.6%.

7. The permeable concrete containing waste glass powder according to claim 1, characterized in that: The waste glass powder comprises, by mass percentage, 70-75% SiO2, 10-15% Na2O, 5-10% CaO, 1-2% Al2O3, 0.5-1% K2O, 0.05-0.1% Fe2O3 and 3-4% impurities.

8. The method for preparing permeable concrete containing waste glass powder according to any one of claims 1 to 7, characterized in that: The following steps are involved: Natural aggregate, coal gangue and 5-10wt% water are mixed and stirred for 20-40s, followed by adding cement, waste glass powder and silica fume and continuing to stir for 50-70s. Finally, the remaining water is added and stirred for 110-130s to obtain the finished concrete.